2020
DOI: 10.1515/biol-2020-0047
|View full text |Cite
|
Sign up to set email alerts
|

LINC00202 promotes retinoblastoma progression by regulating cell proliferation, apoptosis, and aerobic glycolysis through miR-204-5p/HMGCR axis

Abstract: AbstractLINC00202 is a newly identified long noncoding RNA (lncRNA) and has been demonstrated to involve in the progression of retinoblastoma (RB). Here, we further explored the role and the underlying molecular mechanism of LINC00202 on RB malignant properties and glycolysis. LINC00202, microRNA (miR)-204-5p, and 3-hydroxy-3-methyl-glutaryl-coenzyme A reductase (HMGCR) mRNA were detected by a quantitative real-time polymerase chain reaction. Cell proliferation and apoptosis we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…For example, the expression of miR-204 in Rb patients is dysregulated, and its expression level is related to optic nerve infiltration, lymph node metastasis, and tumour tissue differentiation. miR-204 may affect the proliferation and apoptosis of Rb cells, thereby affecting the development of Rb, which may become an early stage molecular indicator for diagnosing and evaluating the prognosis of Rb (43)(44)(45); miR-338-5p is up-regulated in the serum of patients with Rb, which may play a role in promoting cancer in the occurrence and development of Rb, and has the potential value of the early diagnosis of Rb (46,47). Recent studies have shown that dysregulated miR-592 and miR-217-3p have been reported to be involved in developing many different types of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the expression of miR-204 in Rb patients is dysregulated, and its expression level is related to optic nerve infiltration, lymph node metastasis, and tumour tissue differentiation. miR-204 may affect the proliferation and apoptosis of Rb cells, thereby affecting the development of Rb, which may become an early stage molecular indicator for diagnosing and evaluating the prognosis of Rb (43)(44)(45); miR-338-5p is up-regulated in the serum of patients with Rb, which may play a role in promoting cancer in the occurrence and development of Rb, and has the potential value of the early diagnosis of Rb (46,47). Recent studies have shown that dysregulated miR-592 and miR-217-3p have been reported to be involved in developing many different types of cancer.…”
Section: Discussionmentioning
confidence: 99%